1972
DOI: 10.1172/jci107095
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Symptomatic Insulin Reactions after Fasting

Abstract: A B S T R A C T This study was carried out to determine if, in fasting, an adaptation to utilization of ketones could prevent cerebral dysfunction during periods of acute, insulin-induced glucopenia.In the course of standard insulin tolerance tests (0.1-0.2 U/kg), nine obese subjects manifested frank hypoglycemic reactions resulting in an increase in urinary catecholamine excretion from 61 to 113 ttg/24 hr (P < 0.01). After fasting 2 months, administration of weightadjusted doses of insulin produced identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 21 publications
2
63
0
Order By: Relevance
“…However, in a recent study [10] in which adrenal vein epinephrine levels were examined in response to insulin hypoglycemia, it was found that intracarotid infusion of /J-hydroxybutyrate inhibited the epinephrine response to hypoglycemia. Drenick and co-workers [6] have furthermore shown no increase in catecholamine excretion after insulin-induced hypoglycemia in prolonged fasted (and thus hyperketonemic) man. Such data suggest that the appropriate brain center responsive to hypoglycemia no longer "recognizes" this state when provided with an alternate energy substrate in the form of ketone bodies.…”
Section: Discussionmentioning
confidence: 94%
“…However, in a recent study [10] in which adrenal vein epinephrine levels were examined in response to insulin hypoglycemia, it was found that intracarotid infusion of /J-hydroxybutyrate inhibited the epinephrine response to hypoglycemia. Drenick and co-workers [6] have furthermore shown no increase in catecholamine excretion after insulin-induced hypoglycemia in prolonged fasted (and thus hyperketonemic) man. Such data suggest that the appropriate brain center responsive to hypoglycemia no longer "recognizes" this state when provided with an alternate energy substrate in the form of ketone bodies.…”
Section: Discussionmentioning
confidence: 94%
“…However, after 3-7 days of starvation, ketone-body utilization increases substantially, accounting for 50-85% of total oxidative metabolism in skeletal muscle (2,6). With continuing starvation, a decline in ketone-body utilization by skeletal muscle has been observed, so that after 24 days of fasting, the net uptake of AcAc plus fi-OHB accounts for 0-16% of muscle oxidative metabolism (2,7,8). The circulating arterial concentration of total ketone bodies in obese subjects increases from 2-3 mmol/liter after 3 days of starvation to 7-8 mmol/liter after 24-42 days of continuous starvation (1, 2).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that after 3-7 days of starvation, ketone bodies were the preferred fuels for skeletal muscle, accounting for 50-85% of muscle oxidative metabolism in obese and lean subjects (2,6). However, it was observed in obese subjects that after more prolonged periods of starvation, free fatty acids (FFA) were preferentially utilized by muscle, and only a small net uptake of ketone bodies occurred (2,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…These data were interpreted to suggest that after a period of adaptation the human brain could convert to the use of ketones as a metabolic fuel. These observations received support from clinical observations that hypoglycaemia appeared to be better tolerated in persons after prolonged fast [28] but the idea remained that a period (unspecified) of adaptation was required for the brain to switch on the necessary enzyme systems. This was despite an elegant study in rodents [29] that demonstrated equal evidence of brain ketone utilisation in rats made acutely hyperketonaemic by ketone infusion as in animals made subacutely ketonaemic by prolonged fasting.…”
Section: Brain Metabolism and Hypoglycaemiamentioning
confidence: 99%